Pentingnya melatih problem solving pada anak usia dini melalui bermain - Putri Nadila (Pedagogi: Jurnal Ilmu Pendidikan, 2021)
This study is a literature study that aims to determine the importance of practicing problem solving in early childhood through play. This study uses various written sources such as articles, journals, and documents that are relevant to what will be examined in this study. The results obtained in this study are that the introduction of problem solving to children from an early age is very important to do because it can make children think critically, systematically and get children used to looking for answers to problems and draw conclusions without haste. Games that can be done in instilling the spirit of prolem solving in anank are fuzzle, muse, unloading and so on.